Educational trajectories within and beyond the core education phase in Switzerland: a sequence analysis based on SHP data 1999–2023 - Edler, Susanne; Hadjar, Andreas (Frontiers in Sociology, 2025)
IntroductionSwitzerland's educational expansion has lagged behind other industrialized countries, with fewer youths attending upper secondary schools and attaining tertiary education. This paper examines individual educational trajectories over a long period, considering later achievements and higher vocational qualifications. It also identifies inequalities in educational trajectory patterns based on social and migration background, as well as gender.MethodsUsing Swiss Household Panel (SHP) data from 1999 to 2023, the sample includes 2,580 individuals born between 1939 and 1983.ResultsFindings show an extended education phase over time, with increased higher education and vocational training. Fewer individuals completed their education by age 21 in the 1969–83 cohort compared to earlier cohorts. Three clusters were identified for the 1939–53 cohort, six for the 1954–68 cohort, and three again for the 1969–83 cohort, indicating diversification.DiscussionEducational trajectory patterns vary significantly among different social groups, highlighting profound inequalities.